Thermomechanical effect of vertical well drilling in salt rocks in selected cases. Issue 5 (6th July 2015) - Lira, William Wagner Matos; Gonçalves, Giancarlo de Gusmão; Araujo, Catarina Nogueira; Ramos Junior, Adeildo Soares; Frery, Alejandro César
Abstract : Purpose: – The purpose of this paper is to present an analysis of the effect of the temperature on the creep deformation during vertical well drilling in salt rocks in selected cases. Design/methodology/approach: – The authors performed numerical simulations by Finite Element Method, using non-linear viscoelastic models and weak thermomechanical coupling. The authors evaluated, in selected cases, the effect of temperature during salt rock vertical well drilling. Numerical examples were performed to validate the studies. More specifically, the authors considered the problem of vertical well drilling for oil exploration below these salt layers. Findings: – The authors concluded that the biggest reduction in the wellbore closure rate occurs when the wellbore is at low temperature with respect to the rock initial. This is due to two factors, namely, a reduced salt viscous strain rate and the thermal strain contrary to the well radial closure caused by the temperature variation. Beyond the creep effect, the thermal strain also affects the stress in the creep constitutive equation. Practical implications: – With recent oil discoveries in deep water, for example, in the pre-salt, where temperatures are high, the study of the influence of temperature is important, since it contributes to the increase of the creep. The results here presented are relevant, although the engineering aspects of a practical solution for reducing the wellbore displacement based on temperature variation is challenging. Such approach requires cooling mechanisms that delay the heating of the drilling fluid, which is surrounded by rocks at high temperature. Originality/value: – The main contribution of this paper is to present a numerical study, in selected cases, of the effect of temperature on the creep deformation during vertical well drilling in salt rocks, analyzing a possible reduction of these deformations when subjected to a temperature variation.